Pengembangan Kewirausahaan Kreatif Melalui Youtuber: Studi Pada Mahasiswa dan Generasi Z - Utomo, Mohammad Nur; Cahyaningrum, Widyastuti; Islami, Rahmi Nur (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The community service program "Development of YouTuber-Based Entrepreneurship for Students and Generation Z" aims to equip the younger generation with skills and understanding of the potential of digital platforms, especially YouTube. This program includes outreach activities, workshops, mentoring, content development and network collaboration.  Participants gain knowledge about how to utilize social media such as YouTube, Instagram, TikTok and Facebook to develop business. They are also trained in technical skills for creating video content, from shooting to editing. Participants were 30 students on 10 October 2024 at the economics faculty of the University of Borneo, Tarakan. Workshop, namely technical training in creating video content, including shooting, editing and creative strategies. Digital marketing strategies and personal branding are important materials for building a loyal audience and increasing competitiveness. This program emphasizes the principles of creativity, courage, innovation and adaptability as the basis for participants to develop as competent content creators. Mentoring activities involve experienced practitioners, providing practical insights and direction relevant to the digital world. As a result, this program has had a positive impact, helping participants understand opportunities in the digital world to develop sustainable entrepreneurship. It is hoped that this program will continue to develop with wider coverage and updated material for greater benefits.ABSTRAKProgram pengabdian masyarakat "Pengembangan Kewirausahaan Berbasis Pekerja Seni 'YouTuber' pada Mahasiswa dan Generasi Z" bertujuan membekali generasi muda dengan keterampilan dan pemahaman tentang potensi platform digital, khususnya YouTube. Program ini mencakup kegiatan penyuluhan, workshop, mentoring, pengembangan konten, dan kolaborasi jaringan.  Peserta memperoleh pengetahuan tentang cara memanfaatkan media sosial seperti YouTube, Instagram, TikTok, dan Facebook untuk mengembangkan bisnis. Mereka juga dilatih keterampilan teknis pembuatan konten video, dari pengambilan gambar hingga pengeditan. Peserta sebanyak 30 mahasiswa pada 10 oktober 2024 di fakultas ekonomi Universitas Borneo Tarakan. Workshop yaitu dengan Pelatihan teknis pembuatan konten video, termasuk pengambilan gambar, pengeditan, dan strategi kreatif. Strategi pemasaran digital dan personal branding menjadi materi penting untuk membangun audiens yang loyal dan meningkatkan daya saing. Program ini menekankan prinsip kreatif, berani, inovatif, dan adaptif sebagai landasan peserta untuk berkembang sebagai content creator kompeten. Kegiatan mentoring melibatkan praktisi berpengalaman, memberikan wawasan praktis dan arahan relevan dengan dunia digital. Hasilnya, Peserta memahami cara memanfaatkan platform digital, seperti YouTube, Instagram, TikTok, dan Facebook, untuk mendukung pengembangan usaha berbasis seni dan kreativitas.